The Optimization of Contextual Image Media-Based Arabic Language Learning In Rural Madrasah Ibtidaiyah - Nur Aini Aziza; Gusli Bambang Irawan (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2026)
Arabic language learning in Islamic primary education plays a crucial role in developing students’ linguistic competence and supporting their understanding of religious texts; however, in practice, it is often constrained by abstract instructional approaches and limited use of contextual learning media. Previous studies have largely emphasized the effectiveness of visual media in controlled or resource-rich environments, leaving a gap in understanding how such media can be optimized in rural madrasah settings with limited facilities. This study aims to analyze the optimization of Arabic language learning through picture-based media in a rural madrasah ibtidaiyah, focusing on the implementation process, classroom interaction, learning challenges, and teachers’ adaptive pedagogical strategies. The study employed a qualitative case study design conducted in a rural madrasah ibtidaiyah in Tanjung Jabung Timur involving one Arabic language teacher, eight fifth-grade students, and three members of school management. Data were collected through participatory observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings reveal that picture-based media enhances student engagement, strengthens contextual vocabulary comprehension, and encourages changes in classroom interaction from teacher-centered learning toward more student-participatory and student-responsive learning processes. The study also found that the effectiveness of picture-based learning is influenced more by teachers’ pedagogical adaptation and creativity than by the availability of technological facilities. In conditions of limited infrastructure, teachers adapted learning by utilizing simple visual media, contextual explanations, and interactive classroom activities to maintain students’ engagement and understanding. Therefore, this study concludes that picture-based media should not merely be understood as an instructional aid, but as part of an adaptive pedagogical strategy that supports meaningful, contextual, and participatory Arabic language learning in resource-limited rural madrasah settings. These findings provide both theoretical and practical contributions to the development of visual media-based Arabic language instruction in primary Islamic education. Keywords:  Arabic language learning; visual media; picture-based learning; pedagogical adaptation; rural madrasah.